(untitled) (Journal of Parents and Teachers, 2017)
The Catholic Scout Movement is proposed as the educational response to the children and young people of Spanish society under the values of Jesus of Nazareth as an example of life. Today we are, with great difference, the movement of infancy and youth that has more members in the Spanish Church.